Assessing the Treatment of Mixed Landfill Leachate and Urban Wastewater using Various Electrode Arrangements in the Electrochemical Coagulation Process - Maede Ramezani; Hassan Rezaei; Mohsen Jahanshahi; hajar Abyar (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Leachate of the urban waste landfill is one of the most contaminated wastewaters that can pollute surface and groundwater sources, especially the environment. The production trend of urban wastewater is also increasing with a sharp rise in population and the development of urbanization. To address this environmental issue, the present study aimed to consider the simultaneous treatment of mixed landfill leachate and urban wastewater using the electrochemical coagulation process. Methods: The present laboratory study was carried out on the effluent produced from the landfill and urban wastewater produced in Qaemshahr. In this study, effective parameters in the electrochemical coagulation process, including the type of electrodes (iron and aluminum), electrode arrangement (monopolar series-parallel and bipolar series), current intensity (0.5, 1, and 2 amperes), and the initial pH of the wastewater (3.2, 6.1, and 11.4) were investigated for the reduction of chemical oxygen demand (COD) in wastewater containing a mixture of landfill leachate and urban wastewater (in equal proportions). After the appropriate electrode selection under default conditions (current intensity of 1 ampere, wastewater pH, and a duration of 120 min), the impacts of the current intensity and the initial pH of the wastewater on the COD removal rate in various electrode arrangements were assessed. Furthermore, the results were reported after three repetitions for validation purposes. Results: Under optimal conditions, the iron electrode in a monopolar series arrangement with a current intensity of 2 amperes under the wastewater pH and a duration of 120 min resulted in a 57.8% COD removal. Conclusion: Regarding the acceptable performance of the electrochemical coagulation process, it is possible to utilize its potential to treat municipal wastewater and landfill leachate.